Glenwood Hot Springs : Hotel Colorado (New York : Alvin Devereux, 1964)
Reprint of advertising brochure, its "original publication dating from the early 1900s ... "issued about 1909 or perhaps a little later".
Glenwood Hot Springs Company, The Hotel Colorado Company, E.E. Lucas, manager
Keywords: Colorado -- History; Glenwood Springs (Colo.) -- History